Development of Root Caries Associated With the Use of Sugar-Free Nicotine Lozenges: A Long-Term Case Report - Ehrhardt, Coral; Mäkinen, Kauko K.; Cobb, Charles M. (WILEY, 2025)
The authors present a case concerning an adult male patient who developed multiple sites of root caries adjacent to the area where he habitually held a sugar-free nicotine lozenge that contained mannitol and maltodextrin. The root caries occurred despite the patient's excellent oral hygiene, exemplary dietary habits, and clinically normal salivary flow. Between 1999 and 2008, he had only required two restorations to repair carious lesions. This patient had a 20+-year habit of using smokeless tobacco before switching to a cessation aid nicotine lozenge in May of 2008. A full-mouth series of radiographs taken in November 2009 revealed carious lesions on virtually every posterior tooth. The nicotine lozenge's principal ingredients were mannitol (75.7%) and maltodextrin. According to the United States' current Food and Drug Administration (FDA) guidelines, manufacturers can advertise these lozenges as sugar-free. Thus, it is assumed by the public that these types of products are incapable of "causing a cavity." However, this case report presents evidence suggesting that frequent use of sugar-free nicotine lozenges may be associated with dental caries.